Single-cell transcriptomes of developing and adult olfactory receptor neurons in Drosophila - Colleen N McLaughlin; Maria Brbić; Qijing Xie; Tongchao Li; Felix Horns; Sai Saroja Kolluru; Justus M Kebschull; David Vacek; Anthony Xie; Jiefu Li; Robert C Jones; Jure Leskovec; et al. (eLife, 2021)
Recognition of environmental cues is essential for the survival of all organisms. Transcriptional changes occur to enable the generation and function of the neural circuits underlying sensory perception. To gain insight into these changes, we generated single-cell transcriptomes of Drosophila olfactory- (ORNs), thermo-, and hygro-sensory neurons at an early developmental and adult stage using single-cell and single-nucleus RNA sequencing. We discovered that ORNs maintain expression of the same olfactory receptors across development. Using receptor expression and computational approaches, we matched transcriptomic clusters corresponding to anatomically and physiologically defined neuron types across multiple developmental stages. We found that cell-type-specific transcriptomes partly reflected axon trajectory choices in development and sensory modality in adults. We uncovered stage-specific genes that could regulate the wiring and sensory responses of distinct ORN types. Collectively, our data reveal transcriptomic features of sensory neuron biology and provide a resource for future studies of their development and physiology.